2013
DOI: 10.1002/bies.201300108
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress as a cost of reproduction: Beyond the simplistic trade‐off model

Abstract: The idea that oxidative stress may underpin life history trade‐offs has become extremely popular. However, experimental support for the concept has proved equivocal. It has recently been suggested that this might be because of flaws in the design of existing studies. Here, we explore the background to the oxidative stress hypothesis and highlight some of the complexities in testing it. We conclude that the approach recently suggested to be least useful in this context (comparing reproducing to non‐reproducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
280
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(293 citation statements)
references
References 105 publications
(154 reference statements)
11
280
2
Order By: Relevance
“…While factors that increase metabolic rate have been linked to an increase in oxidative damage (e.g. immune challenges, van de Crommenacker et al, 2010;exercise, Costantini et al, 2008b), recent work strongly suggests that increased metabolic rate per se is unlikely to drive increases in ROS and, thus, oxidative damage (reviewed in Speakman and Garratt, 2014;Salin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While factors that increase metabolic rate have been linked to an increase in oxidative damage (e.g. immune challenges, van de Crommenacker et al, 2010;exercise, Costantini et al, 2008b), recent work strongly suggests that increased metabolic rate per se is unlikely to drive increases in ROS and, thus, oxidative damage (reviewed in Speakman and Garratt, 2014;Salin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, if eating results in an increase in oxidative damage beyond the animal's ability to neutralize this oxidation, then oxidative damage should be detectably higher during absorption. By investigating links between eating and oxidative physiology, we evaluate the extent to which postprandial oxidative stress exists in non-human animals, thus informing discussions regarding how oxidative physiology interfaces with life history theory (Dowling and Simmons, 2009;Speakman and Garratt, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that in two rodent species during reproduction, superoxide dismutase was downregulated in the blood, paralleling the increased damage, and upregulated in the liver, paralleling the reduced damage (Plumel et al., 2014; Xu et al., 2014; Yang et al., 2013). This may suggest that during reproduction, females may differentially allocate protection between different tissues (Speakman & Garratt, 2013). It may be speculated that protection of “solid” tissues is more important for animal performance than of blood plasma because the turnover of plasma constituents is high.…”
Section: Discussionmentioning
confidence: 99%
“…The investment in reproduction may reduce allocation of resources to somatic protection against ROS and repair mechanisms that would lead to oxidative damage to tissues. The idea that oxidative damage (to lipids, proteins, and DNA) is a consequence of reproductive effort has been extensively studied in recent years, but has received mixed support (Blount, Vitikainen, Stott, & Cant, 2016; Metcalfe & Monaghan, 2013; Monaghan, Metcalfe, & Torres, 2009; Selman, Blount, Nussey, & Speakman, 2012; Speakman & Garratt, 2013; Speakman et al., 2015). The general picture from studies on various species is very diverse: from an increase in the oxidative stress during reproduction (Alonso‐Alvarez et al., 2004; Bergeron et al., 2011; Fletcher et al., 2013) through the lack of significant differences between breeders and nonbreeders (Nussey, Pemberton, Pilkington, & Blount, 2009; Vitikainen et al., 2016), to the decrease in oxidative stress in breeding individuals (Costantini, Casasole, & Eens, 2014; Garratt, Pichaud, King, & Brooks, 2013; Garratt et al., 2011; Ołdakowski, Wasiluk, Sadowska, Koteja, & Taylor, 2015; Ołdakowski et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation